RECYCLING OF CONTINENTAL CRUST INTO THE MANTLE AS REVEALED BY KYTLYM DUNITE ZIRCONS, URAL MTS, RUSSIA - Bea F.; Fershtater G.B.; Montero P.; Whitehouse M.; Levin V.Y.; Scarrow J.H.; Austrheim H.; Pushkariev E.V. (My University, 2001)
The presence of zircons of crustal origin in the dunites of Kytlym, a subduction-related concentrically zoned dunite–clinopyroxenite–gabbro massif of the Urals Platinum-Bearing Belt, may provide the first direct evidence of the recycling of continental crust into the mantle. Zircons were part of subducted sediments that melted to produce silicic magmas with entrained restitic zircons. These melts induced partial melting in the overlying mantle, which later crystallized as the Kytlym massif. Zircons rapidly captured into early formed dunites were prevented from dissolving completely and underwent different degrees of recrystallization. A few crystals still record their original ages, which range from ∼410 Myr to ∼2800 Myr, thus revealing a different origin. The majority, however, recrystallized in the presence of a limited amount of melt and record the diapir formation, 350–370 Ma, which was coeval with the Uralian high-pressure metamorphism. Lastly, several grains record an age of ∼330 Myr, which is identical, within error, to the Rb–Sr age of the tilaitic gabbros, (337 ± 22 Myr), and may, therefore, represent the crystallization age of the last melts formed during the evolution of Kytlym.